Conditional and Unconditional Conservatism Implications for Accounting Based Valuation and Risky Projects - Nasev, Julia (Quantitatives Controlling, 2009)
At the heart of the current debate on financial reporting standards is conservatism. It is one of the oldest principles in accounting. Most obviously, conservatism is reflected in high market-to-book ratios indicating that accounting measurement understates book value relative to market value. Julia Nasev examines the impact of conservative accounting numbers on valuation estimates and on real economic decisions such as cost stickiness.